The effect of ball carrying method on spinting performance among school rugby player / Muhammad Dinie Danial Herman - Herman, Muhammad Dinie Danial (2019)
The purpose of this study is to investigate the effect of ball carrying method on sprinting performance among school rugby player. Forty rugby players (N=40) from Sekolah Menengah Kebangsaan King George V performed 2 x 30 meters sprint under two conditions: one-handed method and two-handed method. The time taken for the test started at the initial 10 meters until the final 20 meters. The study compared the differences in time between one-handed and two handed method of ball carrying. One Sample T-Test and Paired Sample T-Test were used in this study to analyze the data of the subjects. Based on One Sample T-Test result, there was a significant effect one-handed method (p = 0.000) and two-handed method (p = 0.000) of ball carrying on sprinting performance. The result of the study also showed that one-handed method (M = 2.4730, SD = 0.35180) was inferior to two-handed method (M = 2.6548, SD = 0.39813). To conclude, this finding suggests one-handed method was faster compared to two handed method, but both method have their own advantages which the player may apply fending strategies while holding the ball with one hand or the player may pass the ball to their teammates while holding the ball with two hands.